Diagnostic Performance of 60 MHz High-Definition Intravascular Ultrasound versus Fourier Domain Optical Coherence Tomography for Identifying Plaque Rupture, Plaque Erosion, and Thrombosis in a Rabbit Model - Gang Wang; Weishen Qiao; Chun Xing; Zhibo Yao; Yufei Sun; Xingtao Huang; Xuedong Wang; Qi Liu; Ruoxi Zhang; Xing Luo; Yongmei Yu; Jiannan Dai; et al. (Reviews in Cardiovascular Medicine, 2023)
Background: Most acute coronary syndromes occur due to coronary thrombosis caused by plaque rupture (PR) and plaque erosion (PE). Precise in vivo differentiation between PR and PE is challenging for intravascular imaging. This study is the first to determine the diagnostic performance of the novel 60 MHz high-definition intravascular ultrasound (HD-IVUS) for differentiating atherosclerotic plaque morphology influenced by local hemodynamic flow in rabbits. This study evaluated the diagnostic performance of 60 MHz HD-IVUS in identifying thrombosis in rabbits. Methods: We established 60 rabbit models of atherosclerosis with left common carotid artery (LCCA) stenosis and 30 FeCl3-induced LCCA thrombosis. Intravascular imaging was assessed with 60 MHz HD-IVUS and fourier-domain optical coherence tomography (FD-OCT). The present study investigated the diagnostic accuracy of 60 MHz HD-IVUS for PR and PE, as well as thrombosis, using OCT-diagnosis as a standard reference. Results: 60 MHz HD-IVUS for identifying atherosclerotic plaque morphology using plaque cavity and minor intimal irregularities showed high sensitivity and specificity; 92.0 and 90.0% for identifying OCT-defined PR, and 80.0 and 70.0% for OCT-defined PE, respectively. In a rabbit thrombus model, 60 MHz HD-IVUS showed high sensitivity (88.0%) and specificity (80.0%) in identifying OCT-defined thrombosis. Conclusions: 60 MHz HD-IVUS can accurately identify PR and thrombosis. Further studies should confirm the clinical value of this novel technique in PE diagnosis.